2013
DOI: 10.1684/ecn.2013.0337
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of hesperidin, a citrus flavonone, in rats counteracts the oxidative stress, the inflammatory cytokine production, and the hepatotoxicity induced by the ingestion of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)

Abstract: The objective of the current study was to investigate the protective effects of hesperidin against oxidative stress, altered cytokines levels and histological changes in rats induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Rats were divided randomly into four equal groups (Control, TCDD, hesperidin and TCDD+hesperidin). TCDD and hesperidin were given by gavage, dissolved in corn oil at doses of 2 /kg/week and 50 mg/kg/day respectively. The blood and tissue samples were taken from all rats on the 60 th d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…which are involved in tumour progression . Hesperidin (50 mg/kg) treatment reverted the levels of TNF-␣ and IL-1␤ in the carcinogen TCDD treated rats (Bentli et al, 2013). Similarly, administration of Citrus Juices (rich in Hesperidin) in NKK (4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone) induced Lung and colon carcinogenesis in rat and mouse showed down-regulation of mRNA expression of different cytokines (TNF-␣, IL-1␤, IL-6) and inflammatory enzymes (COX-2 and iNOS) and up-regulation of mRNA expression of Nrf2 (Nuclear factor-2) and glutathione S-transferase and quinine reductase which clearly confirmed the anti-inflammatory mechanism of hesperidin against NKK induced cancer (Tanaka et al, 2011).…”
Section: Effect Of Hesperidin On Cancer Associated Inflammation and Omentioning
confidence: 94%
“…which are involved in tumour progression . Hesperidin (50 mg/kg) treatment reverted the levels of TNF-␣ and IL-1␤ in the carcinogen TCDD treated rats (Bentli et al, 2013). Similarly, administration of Citrus Juices (rich in Hesperidin) in NKK (4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone) induced Lung and colon carcinogenesis in rat and mouse showed down-regulation of mRNA expression of different cytokines (TNF-␣, IL-1␤, IL-6) and inflammatory enzymes (COX-2 and iNOS) and up-regulation of mRNA expression of Nrf2 (Nuclear factor-2) and glutathione S-transferase and quinine reductase which clearly confirmed the anti-inflammatory mechanism of hesperidin against NKK induced cancer (Tanaka et al, 2011).…”
Section: Effect Of Hesperidin On Cancer Associated Inflammation and Omentioning
confidence: 94%
“…Hesperidin, a flavanone glycoside, is found abundantly in lemons and oranges . Previous reports have confirmed the antioxidant activity and radical scavenging properties of hesperidin using a variety of assay systems . In addition, Watanabe et al.…”
Section: Introductionmentioning
confidence: 91%
“…They assured that a dose of 50 mg/kg/day HDN for 10 consecutive days reversed the oxidative effects of CCl 4 via a significant reduction of thiobarbituric reactive substances (TBARS) levels and stimulating the antioxidant defense system. Further study has confirmed these results as Bentli et al (2013) who determined that HDN protected the liver against dioxin toxicity and prevented liver injury. In addition, Chen et al (2010) determined that HDN reduced oxidative stress indicators, like ROS and lipid peroxidation, in a dose-dependent manner.…”
Section: Hesperidin (Hdn)mentioning
confidence: 54%